Genetic diversity of Ichthyophthirius multifiliis (Fouquet, 1876) infecting farmed rainbow trout (Oncorhynchus mykiss Walbaum, 1792) in Turkey. Issue 8 (29th April 2022) - Pekmezci, Gokmen Zafer; Yildirim, Alparslan; Duzlu, Onder; Simsek, Emrah; Balta, Fikri; Yardimci, Banu; Onuk, Ertan Emek; Onder, Zuhal; Ciloglu, Arif; Yetismis, Gamze; Yilmaz, Erdal; Inci, Abdullah
Abstract: We assessed genetic diversities among Ichthyophthirius multifiliis (Ich) field isolates collected from farmed rainbow trout ( Oncorhynchus mykiss ) in Turkey. The overall prevalence of Ich was 35.3% (634/1798). Five novel Ich genotypes (ImulTR1 and ImulTR3‒ImulTR6) were described based on mitochondrial cox‐1 and nad1_b genes. The remaining genotype ImulTR2 was identical to the previously reported NY3 (or Ark9 and TW7) genotype from the United States and South Asia. Phylogenetic analysis indicated Turkish Ich isolates separated genetically into at least four distinct groups. Our study presents the first data on the genotypes of Ich in Turkey. We also provide evidence for the wide distribution of the NY3 genotype (or Ark9 and TW7) from the United States and South Asia to Turkey. Genetic diversities within the mitochondrial genes provided adequate resolution for describing novel genotypes and identifying the known genotype within Turkish Ich isolates. Description of the Ich genotypes allows for tracking of pathogen genotypes worldwide. Thus, we can better understand the connections between Ich outbreaks in the fisheries aquaculture.